Metaphysics and science: The will and the analogy in Schopenhauer - Prado, Jorge Luis Palicer do (2015)
This paper investigates Schopenhauer’s resolution to the problem of unity between micro and macrocosm that, according to the philosopher, is the biggest Philosophy enigma. Our attention is toward the modification of Kantian doctrine of the thing-in-itself and to the analogical method present in that resolution. The thesis of will as world’s essence was elaborated between 1809 and 1814, period of the philosopher’s scientific formation. It has permitted to reflect the importance of natural sciences in the development of Schopenhauer’s analogical argument. The greatest motivation in this text consists of comprehending the Will as thing-in-itself concept. The conducting hypothesis states that the referred concept was elaborated from the reflexive method by analogy inspired in Schopenhauer’s scientific studies, and while that, it is part of and analogical view of the reality that excludes any ontological transcendent principle.